Syncope in Acute Pulmonary Embolism. Importance of Early Recognition of Recurrent Syncope as a Manifestation of Acute Bilateral Pulmonary Embolism - Sawalha, Khalid; Huang, Bryan; Khan, Shoaib; Younis, Naveed (Archives of Clinical and Medical Case Reports, 2021)
A 43-year-old female patient with past medical history of superficial DVTs, nicotine dependency, and morbid obesity presented with shortness of breath and syncope. She was found to be tachycardic with elevated D-Dimer. Emergent chest-CT was performed which revealed large bilateral pulmonary emboli. As her vitals were within normal limits at that time, there were no indications for tissue plasminogen activator. Later, patient started having fleeting episodes of bradycardia and hypotension with drop in systolic pressure over 40mmHg on slight movements. Being in a rural hospital with limited resources, the decision was made to transfer the patient. Following the transfer, the patient was pronounced deceased due to complications related to her condition. We report this case to emphasize the importance of early recognition and management with thrombolytic therapy or mechanical thrombectomy if contraindications exist in patients with recurrent syncope in a rural setting.